Sustainable Biodiesel Production from Waste Cooking Oil and Crude Palm Oil Using a Custom Mini Pilot Plant - Alan Ooi Lim Siang; Abdul Mutalib Leman; Dafit Feriyanto; Samir Sani Abdulmalik; Supaat Zakaria (Universitas Mercu Buana, 2024)
The widespread practice of reusing Waste Cooking Oil (WCO) in hawker food stalls, often for multiple frying cycles, presents a significant public health concern due to the degradation of the oil, which can lead to the formation of toxic compounds. These practices not only pose health risks, such as increasing the potential for cardiovascular diseases and cancer, but also contribute to environmental pollution when the oil is improperly disposed of. This study seeks to address these issues by converting WCO, along with crude palm oil (CPO), into biodiesel using a custom-designed mini pilot plant. The biodiesel production process involved a two-step reaction. The first step, esterification, was conducted using a 55:100 alcohol-to-oil volume ratio with 1% by volume sulfuric acid (H₂SO₄) as the acid catalyst, at 60°C, with a reaction time of 30 minutes and a stirring speed of 800 rpm. The second step, transesterification, utilized a 6:1 alcohol-to-oil molar ratio, with 1 wt.% sodium hydroxide (NaOH) as the alkaline catalyst, carried out at 70°C over the course of one hour. These conditions were carefully selected to optimize the conversion efficiency and to minimize the free fatty acid content, which is crucial for achieving a high yield of biodiesel. The results demonstrated that the mini pilot plant is highly effective in producing biodiesel from both WCO and CPO. The study also led to the development of a standard operating procedure (SOP) for the biodiesel production process, ensuring reproducibility and efficiency.